Structural health monitoring using smart devices for damage detection - Cai, Ke Xin (2015)
Recent decades have seen the rapid development of lead zirconate titanate (PZT) as a smart material in electro mechanical impedance (EMI) based structural health monitoring (SHM) technique. In this technique, the PZT transducer is attached to the host structure either by surface bonding or embedding it inside where it acts as both sensor and actuator when subjected to electro mechanical field to result in a unique electromechanical signature. The attachment of transducer to the host structure is mostly accomplished by using adhesive bonding layers, which affect the sensitivity of the transducers to a great extent. However for effective sensitivity the transducer needs to have proper interaction with the host structure irrespective of whether there is a bonding layer or not for getting interrogating signature which serves as an indication of the structural health. In the recent past, researchers started exploring partial bonding layer or bonding layer free PZT transducer based EMI technique. In these cases, the attachment of transducer to the host structure is not by bonding adhesive but by mechanical means such as a thumb force, contact pressure, nut-bolt etc. These provide an alternative strategy where installing transducers becomes a problem. The present FYP focuses on the experimental sensitivity analysis of PZT transducers on the host structure using bonding layer free interaction, using magnet supports. Experimental study is backed by numerical investigations so as to aid the future researchers to explore the options of using bonding free PZT transducers for effective SHM. Root Mean Square Deviation (RMSD) based statistical analysis was conducted to validate experimental findings.